Direct observation of a dark state in lycopene using pump-DFWM - Marek, Marie Sophie; Buckup, Tiago; Motzkus, Marcus (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2011)
We apply pump-degenerate four-wave-mixing (pump-DFWM) for the investigation of the ultrafast internal relaxation of the excited states of lycopene. A unique feature in the pump-DFWM signal, appearing at small temporal delays between the initial pump pulse and the DFWM sequence, provides direct evidence for the participation of an additional excited state located between the S2 and S1 states. Our experimental findings are corroborated by a detailed numerical simulation of lycopene’s pump-DFWM signal using the Brownian oscillator model. A very fast dynamics directly after excitation of the S2 state manifests as a component populated with a time constant of about 20 fs and which decays to S1 with a lifetime of 110 fs. This ultrafast dynamics is discussed under the light of several different models suggested for the relaxation pathway of carotenoids. In this context, we show that the dynamics can be explained in terms of a dark electronic state between the S2 and S1 states.
Gesehen am 10.08.2022